Implementasi Kebijakan Badan Penyelenggara Jaminan Sosial (Bpjs) Kesehatan di Kabupaten Bantul Daerah Istimewa Yogyakarta - Kesmawan, Andri Putra; Mutiarin, Dyah (Journal of Governance and Public Policy, 2014)
The purpose of this study to look at the policy implementation BPJS in Bantul and factors that influence and determinedifferences in the effect of policy towards participants PBI BPJS Health Insurance and Health Insurance PBI participantsnot. The method used is a combination of studies (mix method). The study was conducted in Bantul. Unitresearch conducted at the Office of Health BPJS Branch Yogyakarta, Bantul and Senopati Penembahan HospitalPatient Hospital Penembahan Senopati Bantul. Data collection techniques are observation, interviews, documentation,and questionnaire. Mechanical analysis of this study is to describe the implementation of Board policies BPJSusing qualitative descriptive analysis. To explain the factors that affect product moment correlation analysis was used.Furthermore, in order to explain the effect of policy towards participants PBI BPJS Health Insurance and HealthInsurance PBI participants not using Analysis of Variance (ANOVA) with the type of single classification analysis ofvariance (one way ANOVA). The results of this research, policy implementation in Bantul District Health BPJS implementedvery well. After doing research results diperolehan communication dimension index values of 4.44 (verygood), the dimensions of the resource of 4.59 (very good), the dimensions of the disposition of 4.44 (very good)and the dimensions of bureaucratic structures 4.57 (very good). Variables that affect the implementation of theImplementation of the Social Security Agency (BPJS) Health in Bantul is Context Policy (X2) which is equal to 0839(very strong). Meanwhile Content Policy variable (X1) significant correlation to variable implementation (Y) is smallerthan that of 0768 (very strong). Furthermore, there are differences in the effect of the Health Policy ImplementationBPJS PBI participants Health Insurance and Health Insurance PBI participants not at all the dimensions of the dimensionof participation with the value Fh = 100, the dimension of service to the value of Fh = 100 and a financialdimension to the value of Fh = 100.